Marine Algae Extract (Grateloupia Sparsa) for the Green Synthesis of Co3O4NPs: Antioxidant, Antibacterial, Anticancer, and Hemolytic Activities - Amira K. Hajri; Marzough A. Albalawi; Ifat Alsharif; Bassem Jamoussi (Bioinorganic Chemistry and Applications, 2022)
The aqueous extract of red algae was used for bio-inspired manufacturing of cobalt oxide nanoparticles (Co3O4NPs) and for antioxidant, antibacterial, hemolytic potency, and anticancer activity. Typical, characterization techniques include UV-Vis, SEM, EDAX, TEM, FTIR, XRD, and TGA. Using an X-ray diffraction assay, the size of the Co3O4NPs crystal was determined to range from 23.2 to 11.8 nm. Based on TEM and SEM pictures, biosynthesized Co3O4NPs’ had a homogeneous spherical morphology with a 28.8 to 7.6 nm average diameter. Furthermore, Co3O4NPs biological properties were investigated, including determining the antibacterial potency using the zone of inhibition (ZOI) method and determining the minimal inhibitory concentration (MIC). The antibacterial activity of Co3O4NPs was higher than that of the ciprofloxacin standard. Alternatively, scavenging of DPPH free radical investigation was carried out to test the antioxidant capacitance of Co3O4NPs, revealing significant antioxidant ability. The biosynthesized Co3O4NPs have a dose-dependent effect on erythrocyte viability, indicating that this technique is harmless. Furthermore, bioinspired Co3O4NPs effectively against HepG2 cancer cells (IC50: 201.3 μg/ml). Co3O4NPs would be a therapeutic aid due to their antioxidant, antibacterial, and anticancer properties.